(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2025)
The nature of tailoring production shows that many women tailors who produce clothing to the direct order of personal consumers are artisans. They engage directly in production, either working alone or with the assistance of family members or unrelated apprentices[1]. As a result of the development of new tailoring machines, the business of tailoring began to take new dimension, because the tailored women began to expand the business by establishing modern and new fashion centers such as Farees Couture by Farida Said at Zoo road, Fashion Empire by Zainab Lawal at Yahaya Gusau road established in 2012 and KMM Couture by Khadija Munnir Rabiu at Goron Dutse established in 2014 all within the metropolis. The role of women in textile craftwork within the metropolitan area of Kano cannot be over-emphasized. Kano is endowed with several traditional crafts existing for centuries; those of which we are familiar with include cloth-making, embroidery of stitched men’s cap, tailoring, dyeing, weaving, and spinning to name the most important ones. This paper concentrates on the role of women in modernization and reorganization of textile production mainly tailoring in Kano metropolis by examining how modernization and globalization of tailoring as a trade affected the socio-economic re-orientation of Kano metropolis.